Creación de Politicadas: un nuevo segmento de política para jóvenes en las redes sociales de Instagram y Tiktok de Nexos - Rucoba de la Puente, Annia (2025)
Politicadas is a new segment designed for the Instagram and TikTok accounts of Nexos, the information platform of the Journalism specialty at the University of Lima's School of Communication. The project’s purpose consists in curating political content - a process that involves searching, collecting, filtering, and adding value to the information - to present it in an accessible and attractive manner, encouraging interest among young people and raising awareness about the importance of getting involved in the country's political future. The content is presented in two formats. On Instagram, a 1:45-minute video is published where two hosts, in a conversational manner, explain a current political event briefly but in detail. On TikTok, a clip with the key points of the topic is shared, inviting users to watch the full video on the main Nexos account. To facilitate understanding and maintain the audience's attention, "Politicadas" uses a simple and humorous narrative, complemented with visual and auditory elements that provide dynamism and closeness to the content.